2012
DOI: 10.1363/3700611
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Deprivations and Maternal Care in India

Abstract: Despite concerted efforts by national and local governments, and by nongovernmental and international organizations, the utilization of maternal health services in developing countries is far from universal and varies strongly within and between countries.1 Moreover, income disparity in access to maternal care is widening across and within countries, with poor women receiving fewer services than those who are better off. 2-5 Antenatal visits have multiple benefits-early detection of pregnancy complications, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
3
18
1
Order By: Relevance
“…The 12 articles from India were all original research articles and eight were carried out predominantly among rural populations, 10-17 two related to urban settings 18,19 and two analysed national data. 20,21 This high proportion of studies on the rural population might be related to the facts that in India 74% of the population resides in rural areas and 70% of rural births are at home, assisted by family members or traditional birth helpers. With one exception, 17 all 12 articles mention, if not focus on, the high maternal and neonatal mortality rates in India.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 12 articles from India were all original research articles and eight were carried out predominantly among rural populations, 10-17 two related to urban settings 18,19 and two analysed national data. 20,21 This high proportion of studies on the rural population might be related to the facts that in India 74% of the population resides in rural areas and 70% of rural births are at home, assisted by family members or traditional birth helpers. With one exception, 17 all 12 articles mention, if not focus on, the high maternal and neonatal mortality rates in India.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…22 Alongside this diversity, significant disparities in maternal and infant health exist depending on the person's class, place of residence, wealth and education. 10,18,[20][21][22]37 To evaluate the outcomes of caseload midwifery practice in a socially deprived and ethnically diverse inner-city area India is one of 189 countries committed to the Millennium Development Goal of reducing maternal and neonatal mortality rates by 75% during the period 1990-2015. 10,29 Since 2005, the Indian government has sponsored a cash-incentive scheme to poor and marginalised women to encourage them to give birth in an institution and receive antenatal and postnatal care.…”
Section: Diversity and Disparitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited data from the Caribbean indicate that youth who grow up in structured households with consistent rules and regulations and with supportive and nurturing parents are less likely to engage in risky sexual behaviors (Ishida, 2011). In contrast, unhealthy family dynamics, such as parent–child conflicts, parents’ substance abuse, parents’ first sexual experience being at an early age, low parental supervision and monitoring of adolescents, and an authoritarian parenting style that relies on physical punishment of children are related to risky sexual behaviors (Ishida, 2011).…”
Section: Micro-level Family Dynamics and Youth’s Sexual Attitudesmentioning
confidence: 99%
“…14,15 According to a comprehensive health survey conducted by the World Health Organization among 16,000 youth aged 10–18 in nine Caribbean nations, more than 50% of sexually active males and 25% of sexually active females reported having had their first sexual experience by age 10, and only 53% of males and females had used a condom at last sex. 16 A survey among Jamaican 15–19-year-olds found that 54% of males and 32% of females had had sexual intercourse in the past year; 15 of those, 52% of males and 12% of females had had more than one sexual partner during that period.…”
Section: Sexual Risk Behavior Among Middle Adolescentsmentioning
confidence: 99%